2019
DOI: 10.1111/andr.12684
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted topological properties of brain networks in erectile dysfunction patients owing predominantly to psychological factors: a structural and functional neuroimaging study

Abstract: Introduction Human brain was a complex network of interconnected regions. Recent neuroimaging studies had showed that the disruption of brain connectivity was associated with psychological disorders. Abnormal rich club and robustness of brain networks might have a key role in the pathophysiology of psychogenic erectile dysfunction (pED). Methods Both diffusion and functional magnetic resonance imaging were performed in pED patients and healthy controls (HC). Measures of rich club organization and robustness un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…In addition, they found that these connections are reduced in patients with iED when compared to controls. The latter finding supports an abnormal process of sexual stimuli that can explain, at least partially, the observed sexual impairment in iED …”
supporting
confidence: 70%
See 3 more Smart Citations
“…In addition, they found that these connections are reduced in patients with iED when compared to controls. The latter finding supports an abnormal process of sexual stimuli that can explain, at least partially, the observed sexual impairment in iED …”
supporting
confidence: 70%
“…The latter finding supports an abnormal process of sexual stimuli that can explain, at least partially, the observed sexual impairment in iED. 5 Ejaculation represents a crucial part of male sexual response cycle, which ends with the resolution phase, and similar to what reported for erection, can be considered a spinal reflex integrated by specific central brain, which includes medial pre-optic area, paraventricular hypothalamic nucleus, and the lateral hypothalamus, identified as the excitatory pathways, whereas ventral medulla has been demonstrated to play an inhibitory influence on ejaculation. 9 Interestingly, in the present issue, the same Chen and co-authors reported data-derived DTI even in subjects with ejaculatory dysfunction.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…With the application of neuroimaging technologies, the close correlation between sexuality and the central nervous system (CNS) is becoming clearer (14)(15)(16). Many male sexual dysfunctions, such as ED (17)(18)(19)(20)(21)(22), premature ejaculation (23,24), and anejaculation (25) have been detected to be associated with alterations in the structure and function of the brain. For example, patients with pED demonstrated the atrophied gray matter volume (17,19), altered white matter microstructure (26), aberrant activity patterns (20), and disrupted topological properties (22) in multiple brain regions, such as prefrontal cortex, cingulate cortex, and insular cortex.…”
Section: Introductionmentioning
confidence: 99%